Analisa Terhadap Realisasi Anggaran Pada Perternakan Lele di Rangkas Bitung - Nur, Achmad Fadillah; Monica, Anes; Rasyita, Nazila; R, Rifky; H, Hardiansyah; S, Saridawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Catfish is one of the leading fisheries sectors on the market and has potential for food security as a source of animal protein. This research aims to analyze the catfish cultivation business in Cinihnih Village. The method used in this journal is by conducting observations and interviews, namely by coming directly to the catfish farming place and conducting an interview with Mr. Aryandi in Cinihnih village, Cimarga subdistrict, Rangkasbitung. Based on the results of observations made, catfish are among the fish that live in fresh water so their survival rate is high until harvest. Feeding catfish is free, but you still have to pay attention to the fish's nutrition. The place that must be provided for catfish can use a waring. For the marketed selling price of Rp. 21,000.00/kg. The advantages are getting quite large profits, while the weaknesses and difficulties are the weather factor, inadequate water management and carrying out a filter process (separating large small size catfish).